Finn and the time-traveling pajamas - Buckley, Michael (New York : Delacorte Press, 2021)
After sixty years of trying to stop Paradox and set the universe right again, Finn time-travels to get help from his nine-year-old self.
Keywords: Adventure and adventurers -- Fiction; Monsters -- Fiction; Time travel -- Fiction; Science fiction